A high-efficiency heat storage phase change composite material and preparation method thereof

By introducing hydroxylated graphene into molten salt phase change materials, the thermal conductivity path is formed, and the problem of low thermal conductivity of existing molten salt phase change materials is solved, achieving efficient heat conduction and material performance improvement.

CN115725267BActive Publication Date: 2025-03-18NANJING JINHE ENERGY MATERIALS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211390225.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-08
Publication Date
2025-03-18
Estimated Expiration
2042-11-08

AI Technical Summary

Technical Problem

The existing molten salt phase change materials have low thermal conductivity, resulting in poor heat transfer during application, limiting their further development.

Method used

By dispersing hydroxylated graphene and lithium-based ternary eutectic molten salt well, a thermal conductivity path is formed, and the heat transfer between the graphene and the molten salt is achieved, and the thermal conductivity of the molten salt phase change material is improved.

Benefits of technology

It significantly improves the thermal conductivity of molten salt phase change materials, achieves efficient heat transfer, solves the problem of poor heat transfer, and promotes the application and development of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115725267B_ABST
    Figure CN115725267B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-efficiency heat storage phase-change composite material and a preparation method thereof. A mechanical ball milling method is used to compound high latent heat lithium-based fluoride salt, nitrate and chloride salt in a specific proportion to achieve the design of low-temperature high latent heat eutectic molten salt. Graphene is functionally modified by a strong oxidant to increase the spacing between graphene sheets and improve the agglomeration effect of graphene in molten salt. In addition, the dispersion uniformity of graphene in the composite material is further improved by strong ultrasonic dispersion, forming a low thermal resistance heat conduction path, thereby improving the heat transfer performance of the composite material. The raw materials of the entire phase change material are widely available and the synthesis method is simple, which improves the problem that the current phase change material cannot take into account both high heat storage and high thermal conductivity, realizes the rapid charging and discharging function of the phase change material, and is conducive to the large-scale promotion of heat storage applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy phase change energy storage, and in particular to a high-efficiency heat storage phase change composite material and a preparation method thereof. Background Art

[0002] The huge energy revolution brought about by the "dual carbon" strategy has caused changes in the energy structure. The change from the traditional coal and oil energy structure to the new sustainable development energy structure is an inevitable trend. However, due to the stability and time and space mismatch problems of new energy, the energy utilization rate is greatly reduced. Heat storage technology can store and release heat energy according to demand, effectively making up for the problem of uneven energy supply and demand. Solid-liquid phase change heat storage has quickly developed into a potential heat storage technology due to its advantages such as high phase change latent heat and small heat storage volume.

[0003] Molten salt phase change materials have become heat storage materials with great application prospects due to their good phase change latent heat performance and wide raw material sources. However, they show lower thermal conductivity than metal materials, resulting in poor heat transfer during application, which seriously hinders their further development. 2 Two-dimensional layered carbon materials composed of hybrid carbon atoms have the characteristics of high intrinsic thermal conductivity and high thermal stability, and are widely used in the fields of materials, chemical engineering, power electronics, etc. The two-dimensional structure of graphene is conducive to the rapid transmission of electrons and phonons, and is an ideal thermal conductive filler. However, the intermolecular force of graphene itself is strong and easy to aggregate, which makes it difficult to disperse in molten salt. At the same time, phonon scattering will also occur between graphene and the phase change material matrix, making it difficult to form a continuous and effective heat conduction path in the molten salt, affecting its thermal conductivity enhancement effect and restricting the application of graphene in molten salt phase change materials. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a high-efficiency heat storage phase change composite material which effectively improves the thermal conductivity of the molten salt phase change material by using graphene in view of the deficiencies in the prior art.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A high-efficiency heat storage phase change composite material, comprising a lithium-based ternary eutectic molten salt and hydroxylated graphene; the mass percentage of the hydroxylated graphene is 0.2%-1.5%;

[0007] The lithium-based ternary eutectic molten salt is prepared by compounding lithium-based fluoride salt, chloride salt and nitrate salt.

[0008] The hydroxylated graphene and the ternary eutectic molten salt are well dispersed to form a heat conduction path, achieving efficient heat conduction between the graphene and the molten salt, and effectively improving the thermal conductivity of the molten salt phase change material.

[0009] Specifically, the lithium-based ternary eutectic molten salt is prepared by compounding lithium-based fluoride salt, chloride salt and nitrate in a mass ratio of 1-3:5-10:85-95.

[0010] Preferably, the lithium-based fluoride salt is lithium fluoride, the chloride salt is lithium chloride, and the nitrate salt is lithium nitrate; further preferably, the mass ratio of lithium fluoride, lithium chloride and lithium nitrate is 2:8:90.

[0011] Specifically, the hydroxylated graphene is obtained by modifying graphene with a strong oxidant.

[0012] Furthermore, the present invention also provides a method for preparing the above-mentioned high-efficiency heat storage phase change composite material, comprising the following steps:

[0013] (1) Molten salt blending:

[0014] The lithium-based fluoride salt, the chloride salt and the nitrate salt are mixed by mechanical ball milling to obtain a lithium-based ternary eutectic molten salt;

[0015] (2) Preparation of hydroxylated graphene:

[0016] The graphene nanosheets are dispersed in water to obtain a graphene dispersion, and then the pH of the dispersion is adjusted to 3-4; a strong oxidant is then added to the graphene dispersion, ultrasonically dispersed and modified, and the product is centrifugally filtered and dried to obtain hydroxylated graphene;

[0017] (3) dispersing the hydroxylated graphene obtained in step (2) in an alcohol-water solution to prepare a hydroxylated graphene alcohol-water mixed solution, then adding the lithium-based ternary eutectic molten salt obtained in step (1), ultrasonically dispersing the mixture uniformly, placing the mixture in a drying oven for drying, and grinding the mixture into powder after cooling.

[0018] In step (1), the lithium-based fluoride salt, chloride salt and nitrate salt are placed in a drying oven at 120° C. and dried for more than 12 hours, then mixed and placed on a ball mill for ball milling, and then taken out and sieved to obtain a lithium-based ternary eutectic molten salt.

[0019] Preferably, after the dry lithium-based fluoride salt, chloride salt and nitrate salt are mixed, they are first placed in a mortar for mixing and grinding for 0.5-1 h, and then placed in a ball mill for ball milling at 300-400 r / min for 1-3 h to mix the three molten salts evenly.

[0020] Preferably, in step (2), the graphene nanosheets are added to deionized water and placed in an ultrasonic cell disruptor for ultrasonic dispersion for 2-4 hours to form a uniform graphene dispersion, wherein the concentration of the graphene nanosheets in the graphene dispersion is 1 mg / mL; and the power of the ultrasonic cell disruptor is 800-1000W.

[0021] Specifically, in step (2), the strong oxidant is ferrous chloride and H2O2. Ferrous chloride is added to the graphene dispersion, stirred until the ferrous chloride is completely dissolved, and then placed in an ultrasonic oscillator for ultrasonic dispersion; then H2O2 and deionized water are diluted in a volume ratio of 1:3, and then added into the reaction system at 50 mL / h using a microinjection pump to continue ultrasonic dispersion.

[0022] Specifically, in step (3), the concentration of hydroxylated graphene in the hydroxylated graphene alcohol-water mixture is 0.1-0.5 mg / mL; a lithium-based ternary eutectic molten salt is added to the hydroxylated graphene alcohol-water mixture, ultrasonically vibrated for 1-3 hours, and then dried at 60-80° C. for more than 24 hours.

[0023] Beneficial effects:

[0024] The present invention provides a high-efficiency heat storage phase-change composite material and a preparation method thereof. A mechanical ball milling method is used to compound high latent heat lithium-based fluoride salts, nitrates and chloride salts in a specific proportion to achieve the design of low-temperature and high latent heat eutectic molten salts. Graphene is functionally modified by a strong oxidant to increase the spacing between graphene sheets and improve the agglomeration effect of graphene in molten salts. In addition, the dispersion uniformity of graphene in the composite material is further improved by strong ultrasonic dispersion, forming a low thermal resistance heat conduction path, thereby improving the heat transfer performance of the composite material. The raw materials of the entire phase change material are widely available and the synthesis method is simple, which improves the problem that the current phase change material cannot take into account both high heat storage and high thermal conductivity, realizes the rapid charging and discharging function of the phase change material, and is conducive to the promotion of large-scale heat storage applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0026] Figure 1 It is a DSC curve diagram of the new low-temperature molten salt prepared in Example 1 of the present invention.

[0027] Figure 2 This is a fitting curve diagram of the specific heat capacity of the new low-temperature molten salt prepared in Example 1 of the present invention.

[0028] Figure 3 These are infrared spectra (FTIR) of composite materials with different H2O2 contents prepared in Examples 1-4 of the present invention, wherein (a) is Example 1, (b) is Example 2, (c) is Example 3, and (d) is Example 4.

[0029] Figure 4 2 are DSC curves of composite materials with different H2O2 contents prepared in Examples 1-4 of the present invention, wherein (a) is Example 1, (b) is Example 2, (c) is Example 3, and (d) is Example 4.

[0030] Figure 5 2 is a graph showing the specific heat capacity fitting curves of the composite materials with different H2O2 contents prepared in Examples 1-4 of the present invention, wherein (a) is Example 1, (b) is Example 2, (c) is Example 3, and (d) is Example 4.

[0031] Figure 6 3 and 4. These are DSC curves of composite materials with different GOH contents prepared in Examples 5-7 of the present invention, wherein (a) is Example 5, (b) is Example 6, and (c) is Example 7.

[0032] Figure 7 3 and 4. These are the specific heat capacity fitting curves of the composite materials with different GOH contents prepared in Examples 5-7 of the present invention, wherein (a) is Example 5, (b) is Example 6, and (c) is Example 7.

[0033] Figure 8 It is a thermal conductivity diagram of composite materials with different H2O2 / GOH contents prepared in Examples 1-7 of the present invention. DETAILED DESCRIPTION

[0034] The present invention can be better understood with reference to the following examples.

[0035] The present invention uses a new type of phase change molten salt with high latent heat as a matrix material, and modifies graphene into hydroxylated graphene as a thermal conductivity enhancing material through a strong oxidant. The new phase change molten salt and hydroxylated graphene are compounded through strong ultrasonic dispersion, vacuum drying and other processes to obtain a thermally conductive enhanced composite molten salt phase change heat storage material based on hydroxylated graphene. The hydroxylated graphene composite molten salt phase change material has a low heat storage temperature, high phase change latent heat, and good thermal conductivity. It can realize the rapid heat charging and releasing function of the phase change material, which is conducive to the promotion of large-scale heat storage applications. The specific operating steps are as follows:

[0036] Step 1: Molten Salt Blending

[0037] The new phase-change molten salt is prepared by mixing high latent heat lithium-based fluoride salt, nitrate salt and chloride salt through mechanical ball milling.

[0038] Step 2: Preparation of hydroxylated graphene (GOH)

[0039] Add deionized water to the graphene nanosheets, place them in an ultrasonic cell disruptor for ultrasonic dispersion to form a uniform graphene dispersion; adjust the pH of the dispersion to 3-4 with a 0.1 mol / L dilute HCl solution; weigh ferrous chloride and add it to the graphene dispersion, stir until the ferrous chloride is completely dissolved, and then place it in an ultrasonic oscillator for ultrasonic dispersion; dilute H2O2 and deionized water at a volume ratio of 1:3, and add them to the reaction system at a constant speed. Wash the product after the reaction with dilute HCl, filter it by centrifugation, and dry it to obtain a hydroxylated graphene material;

[0040] Step 3: Preparation of hydroxylated graphene composite molten salt phase change material

[0041] Add an appropriate amount of alcohol-water solution to hydroxylated graphene, and prepare a hydroxylated graphene alcohol-water mixed solution after ultrasonic dispersion. Add a new phase-change molten salt to the above hydroxylated graphene alcohol-water dispersion, and ultrasonically vibrate to evenly disperse the phase-change core material in the above dispersion. Then place the mixed solution in a vacuum drying oven, dry it at 60-80°C for more than 24 hours, and grind the sample into powder after cooling.

[0042] Example 1

[0043] Step 1: Molten Salt Blending

[0044] After the three inorganic salts of lithium fluoride, lithium chloride and lithium nitrate were placed in a drying oven at 120°C for 12 hours, the pure salts of each component were weighed according to the ratio of LiF:LiCl:LiNO3=2:8:90, and the three salts were mixed and ground in a mortar for 0.5-1 hour, and then the ground samples were placed on a ball mill at 300-400r / min for 1-3 hours. Under this condition, the three salts can be mixed evenly. The new phase change molten salt was confirmed to have achieved eutectic by differential scanning calorimetry, and the phase change temperature and phase change latent heat were 243.65°C and 360.19J / g, respectively. Figure 1 shown. Figure 2 Shown is the specific heat capacity fitting curve of the new phase change molten salt, whose average specific heat capacity is 1.19 J / (g·℃). Figure 8 This is the thermal conductivity diagram of the new phase change molten salt, and its thermal conductivity is 0.97W / (m·K).

[0045] Step 2: Preparation of hydroxylated graphene

[0046] Deionized water was added to the graphene nanosheets, and the nanosheets were placed in an ultrasonic cell disruptor and ultrasonically dispersed at an ultrasonic power of 800-1000W for 2-4 hours to form a graphene aqueous dispersion with a concentration of 1mg / mL; the pH of the dispersion was adjusted to 3-4 with a 0.1mol / L dilute HCl solution; 0.98g of ferrous chloride was weighed and added to the graphene dispersion, and the mixture was stirred until the ferrous chloride was completely dissolved and then ultrasonically dispersed in an ultrasonic oscillator; H2O2 and deionized water were diluted in a volume ratio of 1:3, and then injected into the reaction system at a speed of 50mL / h using a microinjection pump. The final injection volume of the H2O2 aqueous solution was 50mL. The product after the reaction was washed with dilute HCl, centrifuged and filtered, and dried to obtain a hydroxylated graphene material. The functional groups and structure of the material were confirmed by Fourier transform infrared technology (FTIR), such as Figure 3 (a). Among them, 1640cm -1 Nearby is the signal peak of C=C functional group, which is the characteristic peak of graphene. 3400cm -1The peak near 1100cm corresponds to the -OH absorption peak, which is the stretching vibration peak of -OH. -1 The absorption peak at corresponds to the stretching vibration peak of CO. The above results indicate the successful preparation of hydroxylated graphene.

[0047] Step 3: Preparation of hydroxylated graphene composite molten salt phase change material

[0048] Add an appropriate amount of hydroxylated graphene to an alcohol-water solution, and prepare a 0.15 mg / mL hydroxylated graphene alcohol-water mixed solution after ultrasonic dispersion. Add a new phase-change molten salt to the above hydroxylated graphene ethanol dispersion to make the content of hydroxylated graphene 0.8%, and ultrasonically vibrate for 1-3 hours to evenly disperse the phase-change molten salt in the above dispersion. Then place the mixed solution in a vacuum drying oven, dry it at 60-80°C for 24 hours, and grind the sample into powder after cooling. Figure 4 (a) is the DSC curve in this embodiment. As shown in the figure, the phase change temperature of the composite material is 237.43°C, and the phase change latent heat is 350.67 J / g, which has a low heat storage temperature and a high phase change latent heat. Figure 5 (a) shows the specific heat capacity fitting curve of the composite material, and its average specific heat capacity is 1.37 J / (g·℃), which is 15.13% higher than that of the phase change molten salt without thermal conductive filler. Figure 8 This is the thermal conductivity diagram of 50mL H2O2 hydroxylated graphene composite molten salt phase change material. Its thermal conductivity is 1.43W / (m·K), which is 47.42% higher than that of the phase change molten salt without thermal conductive filler.

[0049] Example 2

[0050] Step 1: Molten Salt Blending

[0051] The three inorganic salts of lithium fluoride, lithium chloride and lithium nitrate were placed in a drying oven at 120°C and dried for 12 hours, and then the pure salts of each component were weighed according to the ratio of LiF:LiCl:LiNO3=2:8:90. The three salts were mixed and ground in a mortar for 0.5-1 hour, and then the ground sample was placed on a ball mill and mechanically ball-milled at 300-400r / min for 1-3 hours. Under this condition, the three salts can be mixed evenly.

[0052] Step 2: Preparation of hydroxylated graphene

[0053] Deionized water was added to the graphene nanosheets, and the nanosheets were placed in an ultrasonic cell disruptor and ultrasonically dispersed at an ultrasonic power of 800-1000W for 2-4 hours to form a graphene aqueous dispersion with a concentration of 1mg / mL; the pH of the dispersion was adjusted to 3-4 with a 0.1mol / L dilute HCl solution; 0.98g of ferrous chloride was weighed and added to the graphene dispersion, and the mixture was stirred until the ferrous chloride was completely dissolved and then ultrasonically dispersed in an ultrasonic oscillator; H2O2 and deionized water were diluted in a volume ratio of 1:3, and then injected into the reaction system at a speed of 50mL / h using a microinjection pump. The final injection volume of the H2O2 aqueous solution was 100mL. The product after the reaction was washed with dilute HCl, centrifuged and filtered, and dried to obtain a hydroxylated graphene material. The functional groups and structure of the material were confirmed by Fourier transform infrared technology (FTIR), such as Figure 3 (b). Among them, 1640cm -1 Nearby is the signal peak of C=C functional group, which is the characteristic peak of graphene. 3400cm -1 The peak near 1100cm corresponds to the -OH absorption peak, which is the stretching vibration peak of -OH. -1 The absorption peak at corresponds to the stretching vibration peak of CO. The above results indicate the successful preparation of hydroxylated graphene.

[0054] Step 3: Preparation of hydroxylated graphene composite molten salt phase change material

[0055] Add hydroxylated graphene to an appropriate amount of alcohol-water solution, and prepare a 0.15 mg / mL hydroxylated graphene ethanol mixed solution after ultrasonic dispersion. Add a new phase change molten salt to the above hydroxylated graphene ethanol dispersion to make the content of hydroxylated graphene 0.8%, and ultrasonically vibrate for 1-3 hours to make the phase change core material evenly dispersed in the above dispersion. Then place the mixed solution in a vacuum drying oven, dry it at 60-80°C for 24 hours, and grind the sample into powder after cooling. Figure 4 (b) is the DSC curve in this embodiment. As shown in the figure, the phase change temperature of the composite material is 240.00°C, the phase change latent heat is 355.52 J / g, and it has a low heat storage temperature and a high phase change latent heat. Figure 5 (b) shows the specific heat capacity fitting curve of the composite material, and its average specific heat capacity is 1.44 J / (g·℃), which is 21.01% higher than that of the phase change molten salt without thermal conductive filler. Figure 8 This is the thermal conductivity diagram of 100mL H2O2 hydroxylated graphene composite molten salt phase change material. Its thermal conductivity is 2.60W / (m·K), which is 168.04% higher than that of the phase change molten salt without thermal conductive filler.

[0056] Example 3

[0057] Step 1: Molten Salt Blending

[0058] The three inorganic salts of lithium fluoride, lithium chloride and lithium nitrate were placed in a drying oven at 120°C and dried for 12 hours, and then the pure salts of each component were weighed according to the ratio of LiF:LiCl:LiNO3=2:8:90. The three salts were mixed and ground in a mortar for 0.5-1 hour, and then the ground sample was placed on a ball mill and mechanically ball-milled at 300-400r / min for 1-3 hours. Under this condition, the three salts can be mixed evenly.

[0059] Step 2: Preparation of hydroxylated graphene

[0060] Deionized water was added to the graphene nanosheets, and the nanosheets were placed in an ultrasonic cell disruptor and ultrasonically dispersed at an ultrasonic power of 800-1000W for 2-4 hours to form a graphene aqueous dispersion with a concentration of 1mg / mL; the pH of the dispersion was adjusted to 3-4 with a 0.1mol / L dilute HCl solution; 0.98g of ferrous chloride was weighed and added to the graphene dispersion, and the mixture was stirred until the ferrous chloride was completely dissolved and then ultrasonically dispersed in an ultrasonic oscillator; H2O2 and deionized water were diluted in a volume ratio of 1:3, and then injected into the reaction system at a speed of 50mL / h using a microinjection pump. The final injection volume of the H2O2 aqueous solution was 150mL. The product after the reaction was washed with dilute HCl, centrifuged and filtered, and dried to obtain a hydroxylated graphene material. The functional groups and structure of the material were confirmed by Fourier transform infrared technology (FTIR), such as Figure 3 (c) shown. Among them, 1640cm -1 Nearby is the signal peak of C=C functional group, which is the characteristic peak of graphene. 3400cm -1 The peak near 1100cm corresponds to the -OH absorption peak, which is the stretching vibration peak of -OH. -1 The absorption peak at corresponds to the stretching vibration peak of CO. The above results indicate the successful preparation of hydroxylated graphene.

[0061] Step 3: Preparation of hydroxylated graphene composite molten salt phase change material

[0062] Add hydroxylated graphene to an appropriate amount of alcohol-water solution, and prepare a 0.15 mg / mL hydroxylated graphene ethanol mixed solution after ultrasonic dispersion. Add a new phase change molten salt to the above hydroxylated graphene ethanol dispersion to make the content of hydroxylated graphene 0.8%, and ultrasonically vibrate for 1-3 hours to make the phase change core material evenly dispersed in the above dispersion. Then place the mixed solution in a vacuum drying oven, dry it at 60-80°C for 24 hours, and grind the sample into powder after cooling. Figure 4 (c) is the DSC curve in this embodiment. As shown in the figure, the phase change temperature of the composite material is 238.82°C, the phase change latent heat is 349.84 J / g, and it has a low heat storage temperature and a high phase change latent heat. Figure 5(c) shows the specific heat capacity fitting curve of the composite material, and its average specific heat capacity is 1.43 J / (g·℃), which is 20.17% higher than that of the phase change molten salt without thermal conductive filler. Figure 8 This is the thermal conductivity diagram of 150mL H2O2 hydroxylated graphene composite molten salt phase change material. Its thermal conductivity is 2.05W / (m·K), which is 111.34% higher than the specific heat of the phase change molten salt without thermal conductive filler.

[0063] Example 4

[0064] Step 1: Molten Salt Blending

[0065] The three inorganic salts of lithium fluoride, lithium chloride and lithium nitrate were placed in a drying oven at 120°C and dried for 12 hours, and then the pure salts of each component were weighed according to the ratio of LiF:LiCl:LiNO3=2:8:90. The three salts were mixed and ground in a mortar for 0.5-1 hour, and then the ground sample was placed on a ball mill and mechanically ball-milled at 300-400r / min for 1-3 hours. Under this condition, the three salts can be mixed evenly.

[0066] Step 2: Preparation of hydroxylated graphene

[0067] Deionized water was added to the graphene nanosheets, and the nanosheets were placed in an ultrasonic cell disruptor and ultrasonically dispersed at an ultrasonic power of 800-1000W for 2-4 hours to form a graphene aqueous dispersion with a concentration of 1mg / mL; the pH of the dispersion was adjusted to 3-4 with a 0.1mol / L dilute HCl solution; 0.98g of ferrous chloride was weighed and added to the graphene dispersion, and the mixture was stirred until the ferrous chloride was completely dissolved and then ultrasonically dispersed in an ultrasonic oscillator; H2O2 and deionized water were diluted in a volume ratio of 1:3, and then injected into the reaction system at a speed of 50mL / h using a microinjection pump. The final injection volume of the H2O2 aqueous solution was 200mL. The product after the reaction was washed with dilute HCl, centrifuged and filtered, and dried to obtain a hydroxylated graphene material. The functional groups and structure of the material were confirmed by Fourier transform infrared technology (FTIR), such as Figure 3 (d) shown. Among them, 1640cm -1 Nearby is the signal peak of C=C functional group, which is the characteristic peak of graphene. 3400cm -1 The peak near 1100cm corresponds to the -OH absorption peak, which is the stretching vibration peak of -OH. -1 The absorption peak at corresponds to the stretching vibration peak of CO. The above results indicate the successful preparation of hydroxylated graphene.

[0068] Step 3: Preparation of hydroxylated graphene composite molten salt phase change material

[0069] Add hydroxylated graphene to an appropriate amount of alcohol-water solution, and prepare a 0.15 mg / mL hydroxylated graphene ethanol mixed solution after ultrasonic dispersion. Add a new phase change molten salt to the above hydroxylated graphene ethanol dispersion to make the content of hydroxylated graphene 0.8%, and ultrasonically vibrate for 1-3 hours to make the phase change core material evenly dispersed in the above dispersion. Then place the mixed solution in a vacuum drying oven, dry it at 60-80°C for 24 hours, and grind the sample into powder after cooling. Figure 4 (d) is the DSC curve in this embodiment. As shown in the figure, the phase change temperature of the composite material is 238.48°C, the phase change latent heat is 359.17 J / g, and it has a low heat storage temperature and a high phase change latent heat. Figure 5 (d) shows the specific heat capacity fitting curve of the composite material, and its average specific heat capacity is 1.45 J / (g·℃), which is 21.85% higher than that of the phase change molten salt without thermal conductive filler. Figure 8 This is the thermal conductivity diagram of 200mL H2O2 hydroxylated graphene composite molten salt phase change material. Its thermal conductivity is 1.97W / (m·K), which is 103.09% higher than the specific heat of the phase change molten salt without thermal conductive filler.

[0070] Example 5

[0071] Step 1: Molten Salt Blending

[0072] The three inorganic salts of lithium fluoride, lithium chloride and lithium nitrate were placed in a drying oven at 120°C and dried for 12 hours, and then the pure salts of each component were weighed according to the ratio of LiF:LiCl:LiNO3=2:8:90. The three salts were mixed and ground in a mortar for 0.5-1 hour, and then the ground sample was placed on a ball mill and mechanically ball-milled at 300-400r / min for 1-3 hours. Under this condition, the three salts can be mixed evenly.

[0073] Step 2: Preparation of hydroxylated graphene

[0074] Add deionized water to the graphene nanosheets, place them in an ultrasonic cell disruptor and ultrasonically disperse them at an ultrasonic power of 800-1000W for 2-4h to form a graphene aqueous dispersion with a concentration of 1mg / mL; adjust the pH of the dispersion to 3-4 with a 0.1mol / L dilute HCl solution; weigh 0.98g of ferrous chloride and add it to the graphene dispersion, stir until the ferrous chloride is completely dissolved, and then place it in an ultrasonic oscillator for ultrasonic dispersion; dilute H2O2 and deionized water at a volume ratio of 1:3, and inject them into the reaction system at a speed of 50mL / h with a microinjection pump, and the final injection amount of H2O2 aqueous solution is 100mL. The product after the reaction is washed with dilute HCl, centrifuged and filtered, and dried to obtain a hydroxylated graphene material.

[0075] Step 3: Preparation of hydroxylated graphene composite molten salt phase change material

[0076] Add hydroxylated graphene to an appropriate amount of alcohol-water solution, and prepare a 0.15 mg / mL hydroxylated graphene ethanol mixed solution after ultrasonic dispersion. Add a new phase change molten salt to the above hydroxylated graphene ethanol dispersion to make the content of hydroxylated graphene 0.2%, and ultrasonically vibrate for 1-3 hours to make the phase change core material evenly dispersed in the above dispersion. Then place the mixed solution in a vacuum drying oven, dry it at 60-80°C for 24 hours, and grind the sample into powder after cooling. Figure 6 (a) is the DSC curve in this embodiment. As shown in the figure, the phase change temperature of the composite material is 241.33°C, the phase change latent heat is 357.14 J / g, and it has a low heat storage temperature and a high phase change latent heat. Figure 7 (a) shows the specific heat capacity fitting curve of the composite material, and its average specific heat capacity is 1.29 J / (g·℃), which is 8.40% higher than that of the phase change molten salt without thermal conductive filler. Figure 8 This is the thermal conductivity diagram of the hydroxylated graphene composite molten salt phase change material with a GOH content of 0.2%. Its thermal conductivity is 1.16 W / (m·K), which is 19.59% higher than the specific heat of the phase change molten salt without thermal conductive filler.

[0077] Example 6

[0078] Step 1: Molten Salt Blending

[0079] The three inorganic salts of lithium fluoride, lithium chloride and lithium nitrate were placed in a drying oven at 120°C and dried for 12 hours, and then the pure salts of each component were weighed according to the ratio of LiF:LiCl:LiNO3=2:8:90. The three salts were mixed and ground in a mortar for 0.5-1 hour, and then the ground sample was placed on a ball mill and mechanically ball-milled at 300-400r / min for 1-3 hours. Under this condition, the three salts can be mixed evenly.

[0080] Step 2: Preparation of hydroxylated graphene

[0081] Add deionized water to the graphene nanosheets, place them in an ultrasonic cell disruptor and ultrasonically disperse them at an ultrasonic power of 800-1000W for 2-4h to form a graphene aqueous dispersion with a concentration of 1mg / mL; adjust the pH of the dispersion to 3-4 with a 0.1mol / L dilute HCl solution; weigh 0.98g of ferrous chloride and add it to the graphene dispersion, stir until the ferrous chloride is completely dissolved, and then place it in an ultrasonic oscillator for ultrasonic dispersion; dilute H2O2 and deionized water at a volume ratio of 1:3, and inject them into the reaction system at a speed of 50mL / h with a microinjection pump, and the final injection amount of H2O2 aqueous solution is 100mL. The product after the reaction is washed with dilute HCl, centrifuged and filtered, and dried to obtain a hydroxylated graphene material.

[0082] Step 3: Preparation of hydroxylated graphene composite molten salt phase change material

[0083] Add hydroxylated graphene to an appropriate amount of alcohol-water solution, and prepare a 0.15 mg / mL hydroxylated graphene ethanol mixed solution after ultrasonic dispersion. Add a new phase change molten salt to the above hydroxylated graphene ethanol dispersion to make the content of hydroxylated graphene 0.4%, and ultrasonically vibrate for 1-3 hours to make the phase change core material evenly dispersed in the above dispersion. Then place the mixed solution in a vacuum drying oven, dry at 60-80°C for 24 hours, and grind the sample into powder after cooling. Figure 6 (b) is the DSC curve in this embodiment. As shown in the figure, the phase change temperature of the composite material is 241.36°C, the phase change latent heat is 355.37 J / g, and it has a low heat storage temperature and a high phase change latent heat. Figure 7 (b) shows the specific heat capacity fitting curve of the composite material, and its average specific heat capacity is 1.37 J / (g·℃), which is 15.13% higher than the specific heat of the phase change molten salt without thermal conductive filler. Figure 8 This is the thermal conductivity diagram of the hydroxylated graphene composite molten salt phase change material with a GOH content of 0.4%. Its thermal conductivity is 1.23 W / (m·K), which is 26.80% higher than the specific heat of the phase change molten salt without thermal conductive filler.

[0084] Example 7

[0085] Step 1: Molten Salt Blending

[0086] The three inorganic salts of lithium fluoride, lithium chloride and lithium nitrate were placed in a drying oven at 120°C and dried for 12 hours, and then the pure salts of each component were weighed according to the ratio of LiF:LiCl:LiNO3=2:8:90. The three salts were mixed and ground in a mortar for 0.5-1 hour, and then the ground sample was placed on a ball mill and mechanically ball-milled at 300-400r / min for 1-3 hours. Under this condition, the three salts can be mixed evenly.

[0087] Step 2: Preparation of hydroxylated graphene

[0088] Add deionized water to the graphene nanosheets, place them in an ultrasonic cell disruptor and ultrasonically disperse them at an ultrasonic power of 800-1000W for 2-4h to form a graphene aqueous dispersion with a concentration of 1mg / mL; adjust the pH of the dispersion to 3-4 with a 0.1mol / L dilute HCl solution; weigh 0.98g of ferrous chloride and add it to the graphene dispersion, stir until the ferrous chloride is completely dissolved, and then place it in an ultrasonic oscillator for ultrasonic dispersion; dilute H2O2 and deionized water at a volume ratio of 1:3, and inject them into the reaction system at a speed of 50mL / h with a microinjection pump, and the final injection amount of H2O2 aqueous solution is 100mL. The product after the reaction is washed with dilute HCl, centrifuged and filtered, and dried to obtain a hydroxylated graphene material.

[0089] Step 3: Preparation of hydroxylated graphene composite molten salt phase change material

[0090] Add hydroxylated graphene to an appropriate amount of alcohol-water solution, and prepare a 0.15 mg / mL hydroxylated graphene ethanol mixed solution after ultrasonic dispersion. Add a new phase change molten salt to the above hydroxylated graphene ethanol dispersion to make the content of hydroxylated graphene 1.5%, and ultrasonically vibrate for 1-3 hours to make the phase change core material evenly dispersed in the above dispersion. Then place the mixed solution in a vacuum drying oven, dry it at 60-80°C for 24 hours, and grind the sample into powder after cooling. Figure 6 (c) is the DSC curve in this embodiment. As shown in the figure, the phase change temperature of the composite material is 236.54°C, the phase change latent heat is 354.18 J / g, and it has a low heat storage temperature and a high phase change latent heat. Figure 7 (c) shows the specific heat capacity fitting curve of the composite material, and its average specific heat capacity is 1.45 J / (g·℃), which is 21.85% higher than that of the phase change molten salt without thermal conductive filler. Figure 8 This is the thermal conductivity diagram of the hydroxylated graphene composite molten salt phase change material with a GOH content of 1.5%. Its thermal conductivity is 2.00 W / (m·K), which is 106.18% higher than the specific heat of the phase change molten salt without thermal conductive filler.

[0091] The present invention provides a concept and method for a highly efficient heat storage phase change composite material and a preparation method thereof. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A high-efficiency heat storage phase change composite material, characterized in that: It is composed of a lithium-based ternary eutectic molten salt and hydroxylated graphene; the mass percentage of the hydroxylated graphene is 0.8%; The lithium-based ternary eutectic molten salt is prepared by mixing lithium fluoride, lithium chloride and lithium nitrate in a mass ratio of 2:8:90; The hydroxylated graphene is obtained by modifying graphene with a strong oxidant; The phase change temperature of the high-efficiency heat storage phase change composite material is 240.00°C, the phase change latent heat is 355.52 J / g, and the thermal conductivity is 2.60 W / (m·K).

2. The method for preparing the high-efficiency heat storage phase change composite material according to claim 1, characterized in that: The steps include: (1) Molten salt blending: Mixing lithium fluoride, lithium chloride and lithium nitrate in a mass ratio of 2:8:90 by mechanical ball milling to obtain a lithium-based ternary eutectic molten salt; (2) Preparation of hydroxylated graphene: The graphene nanosheets are dispersed in water to obtain a graphene dispersion, and then the pH of the dispersion is adjusted to 3-4; a strong oxidant is then added to the graphene dispersion, ultrasonically dispersed and modified, and the product is centrifugally filtered and dried to obtain hydroxylated graphene; (3) Dispersing the hydroxylated graphene obtained in step (2) in an alcohol-water solution to prepare a hydroxylated graphene alcohol-water mixed solution, then adding the lithium-based ternary eutectic molten salt obtained in step (1), uniformly dispersing the mixture by ultrasonication, placing the mixture in a drying oven for drying, and grinding the mixture into powder after cooling.

3. The method for preparing the high-efficiency heat storage phase change composite material according to claim 2, characterized in that: In step (1), lithium fluoride, lithium chloride and lithium nitrate are placed in a drying oven and dried at 120° C. for more than 12 h, then mixed and placed on a ball mill for ball milling, and then taken out and sieved to obtain a lithium-based ternary eutectic molten salt.

4. The method for preparing the high-efficiency heat storage phase change composite material according to claim 2, characterized in that: After the dried lithium fluoride, lithium chloride and lithium nitrate are mixed, they are first placed in a mortar and ground for 0.5-1 h, and then placed in a ball mill at 300-400 r / min for 1-3 h.

5. The method for preparing the high-efficiency heat storage phase change composite material according to claim 2, characterized in that: In step (2), the graphene nanosheets are added to deionized water and placed in an ultrasonic cell disruptor for ultrasonic dispersion for 2-4 h to form a uniform graphene dispersion liquid, wherein the concentration of the graphene nanosheets in the graphene dispersion liquid is 1 mg / mL; the power of the ultrasonic cell disruptor is 800-1000W.

6. The method for preparing the high-efficiency heat storage phase change composite material according to claim 2, characterized in that: In step (2), the strong oxidants are ferrous chloride and H2O2. Ferrous chloride is added to the graphene dispersion, stirred until the ferrous chloride is completely dissolved, and then placed in an ultrasonic oscillator for ultrasonic dispersion. H2O2 and deionized water are then diluted in a volume ratio of 1:3, and then added into the reaction system at 50 mL / h using a microinjection pump to continue ultrasonic dispersion.

7. The method for preparing the high-efficiency heat storage phase change composite material according to claim 2, characterized in that: In step (3), the concentration of hydroxylated graphene in the hydroxylated graphene alcohol-water mixture is 0.15 mg / mL; lithium-based ternary eutectic molten salt is added to the hydroxylated graphene alcohol-water mixture, ultrasonically shaken for 1-3 h, and then dried at 60-80 °C for 24 h.

Citation Information

Patent Citations

  • Carbon-based phase-change energy storage material and preparation method thereof

    CN109233751A

  • Polyol nano-composite phase change material with high heat storage energy density and power density

    CN115260994A